Relationship between Body Mass Index and Pancreas Volume in Japanese Adults - Kou, Kinsei; Saisho, Yoshifumi; Jinzaki, Masahiro; Itoh, Hiroshi (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Relationship between BMI and pancreas volume.